GROWTH PERFORMANCE, NUTRIENT UTILIZATION, SURVIVAL AND BODY INDICES OF AFRICAN CATFISH (CLARIAS GARIEPINUS, BURCHELL 1822) REARED ON MAGGOT MEAL BASED DIET - Akinwole, A. O.; Dauda, A. B.; Ogunkunle, V. O. (FUDMA Journal of Sciences, 2020)
Growth performance, feed utilization, survival and body indices of African catfish Clarias gariepinus juveniles fed diets containing maggot meal as replacement of fish meal was evaluated for 42 days. Sixty fingerlings of Clarias gariepinus, average weight of 10 g were randomly distributed into six circular tanks at the rate of 10 fish per tank. There were two treatments, DT1(maggot meal-based diet) and DT2 (fish meal-based diet). The fish were fed twice daily. Water quality parameters were monitored on a weekly basis throughout the experimental period. Growth, nutrient utilization and body indices parameters were evaluated at the end of the experiment. Crude protein, crude lipid and ash were higher in the fish meal-based diet (34.65%, 7.33% and 18.03% in DT2 as against 28.70%, 7.20% and 11.0.1% in DT1 respectively), while crude fibre was higher in maggot meal-based diet. The selected water quality parameters: temperature, dissolved oxygen, ammonia and pH were slightly lower in maggot meal based treatment, but none of them was differently significant. Mean weight gain, specific growth rate, protein intake, protein efficiency ratio, lipid intake and lipid efficiency ratio (17.25±0.70 g, 2.39±0.06 %/day, 95.50±1.27 g, 1.81±0.06, 23.96±0.32 g and 7.20±0.24 respectively) were all significantly higher in DT2. The feed conversion ratio was higher significantly in DT1. Survival, hepatosomatic index and condition factor were similar between the two treatments. Though the aforementioned body indices indicated that the total replacement of fish meal with maggot meal is not harmful to the fish, a partial replacement may be better for optimum output